CONTRIBUTOS PARA A DESCRIÇÃO E TRADUÇÃO DO MARCADOR "AINDA POR CIMA" NO PORTUGUÊS EUROPEU CONTEMPORÂNEO - CARAPINHA, Conceição; PLAG, Cornelia; SOUSA, Sara (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Contributions for the description and translation of the discourse marker ainda por cima in contemporary European Portuguese. Based on a cognitive-functional framework, this paper analyses the different uses of the discourse marker ainda por cima in contemporary European Portuguese and, in a second step, its translation into Spanish, French, English, and German. This analysis is based on data collected in two corpora, CETEMPúblico, which allowed the identification of the functions of the marker in European Portuguese, and Europarl, for the listing of its translations. The research carried out in the source language reveals that the marker has an elaborative value, and more specifically an additive value, always associated with an element of unexpectedness, prefacing a new argument that reinforces the conclusion to be reached, which may (or may not) be the strongest argument in an argumentative scale. The contrastive analysis, in turn, shows the great variety of translational solutions adopted and a value not mentioned in any of the monolingual analyses: the counter-argumentative. The text concludes that (i) the different meanings of the marker in Portuguese are quite close and present themselves in a continuum, linked by family resemblances; (ii) there are important challenges in translating DM; (iii) the analysis of translations may require a reinterpretation of the DM in the source text. REZUMAT. Contribuții pentru descrierea și traducerea marcatorului discursiv ainda por cima în portugheza europeană contemporană. Pe baza unui cadru cognitiv-funcțional, această lucrare analizează diferitele utilizări ale marcatorului discursiv ainda por cima în portugheza europeană contemporană și, într-o a doua etapă, traducerea acestuia în spaniolă, franceză, engleză și germană. Această analiză se bazează pe date colectate în două corpusuri, CETEMPúblico, care a permis identificarea funcțiilor marcatorului în portugheză, și Europarl, pentru identificarea traducerilor. Cercetarea efectuată în limba sursă relevă faptul că marcatorul are o valoare elaborativă și, mai precis, o valoare aditivă, asociată întotdeauna cu un element ce exprimă neașteptarea, prefațând un nou argument, care întărește concluzia la care se va ajunge, care poate fi (sau nu) cel mai puternic argument dintr-o scală argumentativă. Analiza contrastivă arată, la rândul ei, marea varietate de soluții de traducere adoptate și o valoare care nu este menționată în niciuna dintre analizele monolingve: contra-argumentativul. Textul concluzionează că (i) diferitele sensuri ale marcatorului în portugheză sunt destul de apropiate și se prezintă într-un continuum, fiind legate prin asemănări de familie; (ii) provocările pe care le ridică traducerea MD sunt semnificative; (iii) analiza traducerilor poate necesita o reinterpretare a MD din textul sursă. Cuvinte-cheie: ainda por cima; marcatori discursivi; traducere; strategii de traducere; analiză contrastivă. Article history: Received 12 August 2023; Revised 19 October 2023; Accepted 30 October 2023; Available online 20 December 2023; Available print 31 December 2023.